Interferon‐free therapy for genotype 1 hepatitis C in liver transplant recipients: Real‐world experience from the hepatitis C therapeutic registry and research network. Issue 1 (January 2016) - Brown, Robert S.; O'Leary, Jacqueline G.; Reddy, K. Rajender; Kuo, Alexander; Morelli, Giuseppe J.; Burton, James R.; Stravitz, R. Todd; Durand, Christine; Di Bisceglie, Adrian M.; Kwo, Paul; Frenette, Catherine T.; Stewart, Thomas G.; et al.
Abstract : Recurrent infection with the hepatitis C virus (HCV) after liver transplantation (LT) is associated with decreased graft and patient survival. Achieving sustained virological response (SVR) with antiviral therapy improves survival. Because interferon (IFN)‐based therapy has limited efficacy and is poorly tolerated, there has been rapid transition to IFN‐free direct‐acting antiviral (DAA) regimens. This article describes the experience with DAAs in the treatment of posttransplant genotype (GT) 1 HCV from a consortium of community and academic centers (Hepatitis C Therapeutic Registry and Research Network [HCV‐TARGET]). Twenty‐one of the 54 centers contributing to the HCV‐TARGET consortium participated in this study. Enrollment criteria included positive posttransplant HCV RNA before treatment, HCV GT 1, and documentation of use of a simeprevir (SMV)/sofosbuvir (SOF) containing DAA regimen. Safety and efficacy were assessed. SVR was defined as undetectable HCV RNA 64 days or later after cessation of treatment. A total of 162 patients enrolled in HCV‐TARGET started treatment with SMV+SOF with or without ribavirin (RBV) following LT. The study population included 151 patients treated with these regimens for whom outcomes and safety data were available. The majority of the 151 patients were treated with SOF and SMV alone (n = 119; 79%) or with RBV (n = 32; 21%), The duration of therapy was 12 weeks for most patients, although 15 patients received 24 weeks of treatment. Of all patients receiving SOF/SMV with or without RBV, 133/151 (88%) achieved sustained virological response at 12 weeks after therapy and 11 relapsed (7%). One patient had virological breakthrough (n = 1), and 6 patients were lost to posttreatment follow‐up. Serious adverse events occurred in 11.9%; 3 patients (all cirrhotic) died due to aspiration pneumonia, suicide, and multiorgan failure. One experienced LT rejection. IFN‐free DAA treatment represents a major improvement over prior IFN‐based therapy. Broader application of these and other emerging DAA regimens in the treatment of posttransplant hepatitis C is warranted. Liver Transpl 22:24‐33, 2016 . © 2015 AASLD.